The Effect of Group-Based Patience Therapy on Reducing Anxiety Levels - Deasy Ratnasari Dewi; Umar Yusuf; Lilim Halimah (Eduvest - Journal of Universal Studies, 2024)
The earthquake at the end of 2022 which occurred in Cugenang Cianjur, West Java, left quite a deep psychological impact on some of the people, especially marked by the emergence of symptoms of anxiety. If intervention is given too late, it will result in more severe psychological disorders. The aim of this research is to examine how much influence patience therapy has on reducing anxiety levels in earthquake victims. The patience therapy used is an approach that integrates targets into aspects biopsikososiospiritual. The research design used is experimental design in the shape of pre test-post test control group design. The population in this study were all students at the Girls' Islamic Boarding School in Cugenang Cianjur. Sampling in this research used Purposive sampling technique. The sample used in this research consisted of 12 subjects who were earthquake survivors in Cugenang Cianjur.A measuring tape used HRS-A Scale from Hamilton which consists of 14 statements which have a validity value of 0.81 and a reliability of 0.91, which includes four aspects, including physiological aspects, cognitive aspects, affective aspects and behavioral aspects. Measurement results on pre test-post test showed a reduction in anxiety levels of 53.4%. Meanwhile, statistical analysis using the independent mann whitney showed a score of 0.00 (p<0.05), which means that patience therapy was significantly effective in reducing anxiety levels in survivors of the earthquake natural disaster in Cugenang Cianjur.